VvMYBA1 and VvMYB3 form an activator–repressor system to regulate anthocyanin biosynthesis in grape - Yang Qin; Changyun Zhang; Xiucai Fan; Jianfu Jiang; Ying Zhang; Jihong Liu; Chonghuai Liu; Lei Sun (Horticultural Plant Journal)
Anthocyanins are important metabolites that provide a red or blue–purple hue to plants. The biosynthesis of these metabolites is mainly activated by the MYB-bHLH-WD40 (MBW) complex and repressed by a wide variety of proteins. Studies have shown that MYB activators activate MYB repressors to balance anthocyanin biosynthesis. However, there is a scarcity of studies investigating this mechanism in grapes. To explore the transcription factors involved in the regulation of anthocyanin biosynthesis, we reanalyzed the RNA-seq database for different developmental stages of ‘Muscat Hamburg’ berries, and the R2R3-MYB gene, annotated as VvMYB3, was screened. Our study revealed the anthocyanin content of the grape cultivar ‘Y73’ was higher than that of its parental cultivar MH, and the putative repressor VvMYB3 was found to be highly expressed in ‘Y73’ by qRT-PCR. The calli transgenic assays demonstrated that the repressive activity of VvMYB3 was conferred by the bHLH-binding motif, as well as by the C1 and C2 motifs. Yeast hybridization and chip-PCR assays revealed that VvMYB3 could repress anthocyanin biosynthesis by competing with VvMYBA1 to bind to VvMYC1 and promoting histone deacetylation of VvUFGT via the C2 motif. However, the expression of VvMYB3 was activated by VvMYBA1, which forms a negative feedback regulatory loop to modulate anthocyanin accumulation. In addition, we found a 408-bp repeat tandem sequence insertion in the VvMYBA1 promoter region of ‘Y73’ by sequencing. The GUS activity analysis showed that this sequence enhanced the expression of VvMYBA1 and led to an excessive accumulation of anthocyanins. Overall, our results provide insights into the anthocyanin activator–repressor system in grapes that prevents overaccumulation of anthocyanins.